Quantitative gait, cognitive decline, and incident dementia: The Rotterdam Study - Sirwan K.L. Darweesh; Silvan Licher; Frank J. Wolters; Peter J. Koudstaal; M. Kamran Ikram; M. Arfan Ikram (2019)
Poor gait has recently emerged as a potential prodromal feature of cognitive decline and dementia. We assessed to what extent various aspects of poor gait are independently associated with cognitive decline and incident dementia.We leveraged detailed quantitative gait (GAITRite™) and cognitive assessments in 4258 dementia-free participants (median age 67 years, 55% women) of the population-based Rotterdam Study (baseline 2009-2013). We summarized 30 gait parameters into seven mutually independent gait domains and a Global Gait score. Participants underwent follow-up cognitive assessments between 2014 and 2016 and were followed up for incident dementia until 2016 (median 4 years).Three independent gait domains (Base of Support, Pace, and Rhythm) and Global Gait were associated with cognitive decline. Two independent gait domains (Pace and Variability) and Global Gait were associated with incident dementia. Associations of gait with cognitive decline and incident dementia were only present in individuals who had been cognitively unimpaired at baseline.Poor performance on several independent gait domains precedes cognitive decline and incident dementia.